2016
DOI: 10.1111/ejh.12822
|View full text |Cite
|
Sign up to set email alerts
|

TPORAs in pITP: description of a case series and analysis of predictive factors for response

Abstract: CR was a significant prognostic factor for the achievement of a DR. Moreover, we observed a trend for DR patients to obtain a subsequent SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…In a single-center study, unlike the others, response (R) was defined as a platelet count C 30 9 10 3 / dL and at least a two fold increase in the baseline count and complete response (CR) as a platelet count C 100 9 10 3 / dL, in the absence of bleeding. In other studies performed, the most accepted response was a platelet count C 50 9 10 3 /dL [4,10,[13][14][15][16][17][18]. The results of our patients revealed that 11/19 (58%) of them reached the platelet count above 30,000/mm 3 while 6/19 (31%) patients were above 50,000/mm 3 .…”
Section: Discussionsupporting
confidence: 51%
“…In a single-center study, unlike the others, response (R) was defined as a platelet count C 30 9 10 3 / dL and at least a two fold increase in the baseline count and complete response (CR) as a platelet count C 100 9 10 3 / dL, in the absence of bleeding. In other studies performed, the most accepted response was a platelet count C 50 9 10 3 /dL [4,10,[13][14][15][16][17][18]. The results of our patients revealed that 11/19 (58%) of them reached the platelet count above 30,000/mm 3 while 6/19 (31%) patients were above 50,000/mm 3 .…”
Section: Discussionsupporting
confidence: 51%
“…These TFR, which have been observed in up to 10–30% of ITP patients receiving these drugs 10 , raise the question of additional potential immunomodulatory properties by increasing the regulatory T and B cell compartment and decreasing platelet destruction 12,13 . To date, there are no predictors to identify in which patients this approach is likely to be successful, other than earlier start of TPO-RA (which may relate to the pathophysiology of the disease), and robust platelet responses 1416 .…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a recent study of 39 patients with ITP treated with TPO-RAs (eltrombopag was used in 11 of them), demonstrated that, after treatment discontinuation, 7 of them (18%) reached a sustained response, defined as the first assessed platelet count ⩾30 × 10 3 /µl available at more than 4 weeks after discontinuation. 61 Notably, this response was achieved in the absence of concomitant or rescue therapies. Among these patients, 71% of them had previously reached a durable response, which was defined as a response (platelet count ⩾30 × 10 3 / µl and at least a twofold increase as compared with the baseline count) or complete response (platelet count ⩾100 × 10 3 /µl with no bleeding) persisting for at least 4 weeks during the treatment period.…”
Section: Eltrombopag Discontinuationmentioning
confidence: 99%